1984
DOI: 10.1357/002224084788520710
|View full text |Cite
|
Sign up to set email alerts
|

Particulate amino acids in the sea: Effects of primary productivity and biological decomposition

Abstract: We measured the flux of amino acids associated with sinking particles collected by sediment traps at two Pacific Ocean sites. These results were compared with results from six other sites where we and others have measured amino acid fluxes. This comparison shows that the flux of amino acids on sinking particles is related to primary productivity. This relationship exists in spite of differences in the oceanic regimes sampled and in the sediment traps, bactericides, and amino acid analysis techniques used. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
2
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(88 citation statements)
references
References 32 publications
(42 reference statements)
10
74
2
1
Order By: Relevance
“…The contribution of these amino acids in marine particles and sediments usually increases with degradation, except for glutamic acid, which decreases with degradation (Lee and Cronin, 1984;Müller et al, 1986;Burdige and Martens, 1988;Lee et al, 2000). In the Florida Keys coral, mole % aspartic acid and glutamic acid in THAA increase with age, while mole % glycine and alanine decrease with age (Fig.…”
Section: Amino Acid Degradation Statementioning
confidence: 93%
“…The contribution of these amino acids in marine particles and sediments usually increases with degradation, except for glutamic acid, which decreases with degradation (Lee and Cronin, 1984;Müller et al, 1986;Burdige and Martens, 1988;Lee et al, 2000). In the Florida Keys coral, mole % aspartic acid and glutamic acid in THAA increase with age, while mole % glycine and alanine decrease with age (Fig.…”
Section: Amino Acid Degradation Statementioning
confidence: 93%
“…The preferential accumulation of glycine and threonine is probably due to their concentration in cell walls (Hecky et al 1973) that are preserved during sinking and decomposition (Siezen and Mague 1978;Lee and Cronin 1984;Müller et al 1986), whereas amino acids that are concentrated in cell plasma (tyrosine, phenylalanine, and glutamic acid) (Hecky et al 1973) tend to be depleted during degradation. Sediment-trap studies sampling POM at increasing depth in the water column confirm these compositional changes of amino acids during decay ( Table 1.…”
Section: Linking Diagenetic Alteration Of Amino Acids and Bulk Organimentioning
confidence: 99%
“…3B), demonstrates the consistency of the DI with well-established indicators of diagenetic alteration. The microbial production of GABA and BALA from their protein precursors and their subsequent preservation in sedimentary deposits has been proposed as a degradation state indicator of marine sediments (Lee and Cronin 1984;Cowie and Hedges 1994). Similarly, hexosamines are generally incorporated into structural biopolymer matrices such as bacterial cell walls and chitinous material (de Leeuw and Largeau 1993) and are enriched in more refractory materials (Dauwe and Middelburg 1998).…”
Section: Linking Diagenetic Alteration Of Amino Acids and Bulk Organimentioning
confidence: 99%
“…A number of studies have reported solubilization/degradation of organic carbon (Gardner et al, 1983;Noji et al, 1999;Honjo et al, 1995), and nitrogen (Hansell and Newton, 1994;Kähler and Bauerfeind, 2001) amino acids (Lee and Cronin, 1984;Lee et al, 1992), fatty acids (Körtzinger et al, 1994), phosphate (Knauer et al, 1984;von Bodungen et al, 1991), dissolved inorganic nitrogen (primarily ammonium, Knauer et al, 1990;von Bodungen et al, 1991), silica (von Bodungen et al, 1991Bauerfeind et al, 1997;Antia et al, 1999), metals (Knauer et al, 1984;Pohl et al, 2004) and particulate barium (Dymond and Collier, 1996). Despite finding that solubilization can account for a substantial proportion of the measured particulate flux, to date there has been no systematic analysis of the corrections that may need to be applied to arrive at values of the entire flux arriving in the trap.…”
Section: Introductionmentioning
confidence: 99%